Authentic Existence In Martin Heidegger: An Appraisal - Agu, Sunny Nzie (PT FORMOSA CENDEKIA GLOBAL, 2023)
Existence has been a central issue among philosophers. This could be because of the unverifiable features which becloud existence. However, martin Heidegger in his philosophical speculations thinks that we should begin with man, since man is the only being that asks question about his own existence or being. He technically called man Dasein. Hence, Dasein is a being in whose very being, being itself is in question. In order to understudy man and how he lives his life, he proposes to analyze man’s existential structures. In his analysis, he discovers that man is the only being in the world that has relation to himself and as well as other beings. Man is not finished product but a possibility to become what he is not yet. Man transcends the present and lives towards the future. This however denotes that man is a free being who projects himself and chooses his own possibility and thereby decides his own mode of life, hence, authentic life. For him authentic life is a life lived in a way one has freely chosen to live. It is a life beyond what is called everydayness and following the crowd. He went further to aver that there are limitations which characterize human existence and they are: falleness, facticity, thrownness, being-with-others, anxiety and so on. In spite of these features, he still averred that man can exist authentically. Hence, this piece adopts hermeneutical and appraisal methods, to argue that authentic existence is realizable amidst these features and structures as aforementioned.